Örgüt Kültürü Tiplerinin Personel Güçlendirmeye Etkisinde Güç Mesafesinin Aracı Rolü - Gün, Gül (Muş Alparslan Üniversitesi, 2019)
Personnelempowerment, which is influenced by organizational culture, is an importantfactor for motivation. As a participatory management, personnel empowerment isdefined as authorization and empowerment of lower-level employees to makedecisions. Hofstede's power distance from cultural dimensions; is explained byemphasizing the power relationship between people. For empowerment practice, itis desired that the level of power in organizations is at a low level. If thereis a high level of power in an organization and employees have this culture, then empowerment practices remain very limited. In this context, this study, conducted in textile enterprises, examines whether the power distance has anintermediary role in the influence of organizational culture types on employeeempowerment. For this purpose, the required data were collected by surveyingemployees from textile enterprises operating in Tunceli province. Correlationand a Structural Equation modelling were applied to all 314 of the data obtained.According to the results of this analysis, the findings supporting the basichypothesis obtained are that culture of adhocracy and personnel empowerment aremediated by the national cultural power distance dimension.

Örgütkültüründen etkilenen personel güçlendirme olgusu, çalışanların güdülenmesindeönemli bir faktördür. Hofstede’in kültür boyutlarından güç mesafesi; kişilerarası güç ilişkisi üzerinde durularak açıklanmaktadır. Güçlendirme uygulamalarıiçin örgütlerde güç mesafesi düzeyinin düşük düzeyde olması istenmektedir. Eğerbir örgütte yüksek düzeyde güç mesafesi mevcutsa, işgörenler bu kültüresahipse, güçlendirme uygulamaları çok sınırlı düzeyde kalabilmektedir. Bubağlamda, çalışmada örgüt kültürü tiplerinin personel güçlendirmeye etkisindegüç mesafesinin aracılık etkisinin olup olmadığı tekstil işletmelerindearaştırılmaktadır. Bu amaçla Tunceli ilinde faaliyet gösteren tekstil işletmesiçalışanlarından anket tekniği ile veri toplanmıştır. Elde edilen 314 adetveriye korelasyon ve yapısal eşitlik modeli uygulanmıştır. Analiz sonuçlarınagöre adhokrasi kültürü ile personel güçlendirme arasında ulusal kültürün güçmesafesi boyutunun aracılık ettiği yönündeki temel hipotezi destekleyicibulgular elde edilmiştir.
The Mediating Role of Power Distance in the Effect of Organizational Culture Teams on the Personnel Empowerment
anemon
Keywords: Organizational Culture Types; Personnel Empowerment; Power distance; Textile operations; Örgüt Kültür Tipleri; Personel Güçlendirme; Güç mesafesi; Tekstil İşletmeleri